Medical Response to a Vinyl Chloride Release From a Train Derailment: New Jersey, 2012. (6th March 2017) - Shumate, Alice M.; Taylor, Jamille; McFarland, Elizabeth; Tan, Christina; Duncan, Mary Anne
Abstract: Objective: The objective of this investigation was to examine the health impact of and medical response to a mass casualty chemical incident caused by a vinyl chloride release. Methods: Key staff at area hospitals were interviewed about communication during the response, the number of patients treated and care required, and lessons learned. Clinical information related to the incident and medical history were abstracted from hospital charts. Results: Hospital interviews identified a desire for more thorough and timely incident-specific information and an under-utilization of regionally available resources. Two hundred fifty-six hospital visits (96.2%) were at the facility closest to the site of the derailment. Of 237 initial visits at which the patient was examined by a physician, 231 patients (97.5%) were treated in the emergency department (ED) and 6 patients (2.5%) were admitted; 5 admitted patients (83.3%) had preexisting medical conditions. Thirteen of 14 asymptomatic ED patients were children under the age of 10 years. One hundred forty-five patients (62.8%) discharged from the ED were diagnosed solely with exposure to vinyl chloride. Conclusions: Continuous emergency response planning might facilitate communication and better distribution of patient surge across hospitals. Individuals with multiple medical conditions and parents and caretakers of children may serve as target groups for risk communication following acute chemical releases. ( Disaster Med Public Health Preparedness . 2017;11:538–544)